2020
DOI: 10.3390/ijms21072596
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Dynamics and Spatial Distribution in Wild-Type and K14 R125P Mutant Cells—A Computational Model

Abstract: Keratins are one of the most abundant proteins in epithelial cells. They form a cytoskeletal filament network whose structural organization seriously conditions its function. Dynamic keratin particles and aggregates are often observed at the periphery of mutant keratinocytes related to the hereditary skin disorder epidermolysis bullosa simplex, which is due to mutations in keratins 5 and 14. To account for their emergence in mutant cells, we extended an existing mathematical model of keratin turnover in wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Still, actin filaments are known to be involved in keratin turnover, e.g., it has been shown that keratin particles originate close to the plasma membrane, at the distal tips of actin stress fibers, and then they translocate continuously along the stress fibers toward the cell center, where they integrate into keratin filament network [23,31]. Upon Cytochalasin-D treatment, which disrupts the actin network, the majority of keratin particles at the cells periphery either disappear or stop almost completely [32]. Also, it has been shown that keratin is closely related to structures at the cell surface, e.g., to focal adhesions [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Still, actin filaments are known to be involved in keratin turnover, e.g., it has been shown that keratin particles originate close to the plasma membrane, at the distal tips of actin stress fibers, and then they translocate continuously along the stress fibers toward the cell center, where they integrate into keratin filament network [23,31]. Upon Cytochalasin-D treatment, which disrupts the actin network, the majority of keratin particles at the cells periphery either disappear or stop almost completely [32]. Also, it has been shown that keratin is closely related to structures at the cell surface, e.g., to focal adhesions [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Keratins can be found in complex polymeric structures of different sizes. For the keratin polymerization dynamics to be mathematically treatable, and analogously to other keratin models [ 13 , 25 ], we group the keratin configurations in few different states depending if it forms very small oligomers (soluble keratin), intermediate size oligomers (particulate keratin) or filaments. In the reaction network presented here, we consider 8 different states: 4 for each keratin species (WT and mutant).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have extended an existing mathematical model for keratin turnover in wild-type cells [ 12 ] to account for the emergence of keratin particles in mutant keratinocytes [ 13 ]. Our model includes the turnover between soluble, particulate and filamentous keratin forms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations